Global scenario of silica-associated diseases: A review on emerging pathophysiology of silicosis and potential therapeutic regimes - Prasad Sherekar; Sanvidhan G. Suke; Archana Dhok; Srikant Malegaonkar; Shrikrishna A. Dhale (Toxicology Reports)
Silicosis is an occupational fibrotic lung disease caused by exposure to respirable crystalline silica dust particles produced during industrial activities. Other crystalline silica-induced pulmonary disorders include a predisposition to mycobacterial infections, obstructive airway diseases, idiopathic pulmonary fibrosis, and lung cancer. This review paper discusses the burden of silicosis and associated co-morbidities in developed as well as developing countries globally using the published data of various government agencies, related organizations, and epidemiological findings. Moreover, it sheds light on diverse mechanisms of silicosis, outlining molecular events and peculiar alterations in lung parenchyma leading to this occupational lung disease. Evaluation of pathophysiological mechanisms could aid in the identification of novel target molecules and treatments; to date, there is no curative treatment for silicosis. In recent periods, a lot of attention has been focused on the development and fabrication of suitable nanocarriers for improved and sustained drug delivery in the pulmonary system. Nanoparticle-based therapeutic modality has been evaluated in in-vitro and ex-vivo silicosis models for prolongation of drug activity and improved therapeutic outcomes. The preclinical findings open the doors to clinical trials for operational and regenerative nanoformulations, which eventually create a positive change in medical practice. The following review summarizes various therapeutic approaches available and in the pipe line for silicosis and also stresses the preventive practices for effectively combating this occupational hazard.